Labor supply on the eve of retirement. Disparate effects of immediate and postponed rewards to working - Christian N. Brinch; Erik Hernæs; Zhiyang Jia (Statistics Norway, Research Department, 2012)
We study two recent changes in incentives to work facing 67-69 year old workers in Norway: an earnings test reform which increases current earnings from work, and a pension system maturation which removes pension accrual from work. Within a difference-in-differences framework, we exploit these changes to investigate the effects of economic incentives. We find the earnings test reform has large effects, while the pension system maturation has no significant effects. The findings confirm that 67-69 year olds can adjust their work efforts to economic incentives, but do so only to thoses related to current income and not to future pensions.
Keywords: J14; H55; 330; labor supply; retirement earnings test; social security wealth; difference-indifferences